Orthologous peramine and pyrrolopyrazine‐producing biosynthetic gene clusters in Metarhizium rileyi, Metarhizium majus and Cladonia grayi. (19th December 2018) - Berry, Daniel; Mace, Wade; Rehner, Stephen A.; Grage, Katrin; Dijkwel, Paul P.; Young, Carolyn A.; Scott, Barry
Summary: Peramine is a non‐ribosomal peptide‐derived pyrrolopyrazine (PPZ)‐containing molecule with anti‐insect properties. Peramine is known to be produced by fungi from genus Epichloë, which form mutualistic endophytic associations with cool‐season grass hosts. Peramine biosynthesis has been proposed to require only the two‐module non‐ribosomal peptide synthetase (NRPS) peramine synthetase (PerA), which is encoded by the 8.3 kb gene perA, though this has not been conclusively proven. Until recently, both peramine and perA were thought to be exclusive to fungi of genus Epichloë ; however, a putative perA homologue was recently identified in the genome of the insect‐pathogenic fungus Metarhizium rileyi . We use a heterologous expression system and a hydrophilic interaction chromatography‐based analysis method to confirm that PerA is the only pathway‐specific protein required for peramine biosynthesis. The perA homologue from M. rileyi ( MR_perA ) is shown to encode a functional peramine synthetase, establishing a precedent for distribution of perA orthologs beyond genus Epichloë . Furthermore, perA is part of a larger seven‐gene PPZ cluster in M. rileyi, Metarhizium majus and the stalked‐cup lichen fungus Cladonia grayi . These PPZ genes encode proteins predicted to derivatize peramine into more complex PPZ metabolites, with the orphaned perA gene of Epichloë spp. representing an example of reductive evolution.